Effectiveness of interventions to improve the public's antimicrobial resistance awareness and behaviours associated with prudent use of antimicrobials: a systematic review. (14th March 2018) - Price, Lesley; Gozdzielewska, Lucyna; Young, Mairi; Smith, Fraser; MacDonald, Jennifer; McParland, Joanna; Williams, Lynn; Langdridge, Darren; Davis, Mark; Flowers, Paul
Abstract: Background: A global antimicrobial resistance (AMR) awareness intervention targeting the general public has been prioritized. Objectives: To evaluate the effectiveness of interventions that aim to change AMR awareness and subsequent stewardship behaviours amongst the public. Methods: Five databases were searched between 2000 and 2016 for interventions to change the public's AMR awareness and/or antimicrobial stewardship behaviours. Study designs meeting the Cochrane Effective Practice and Organization of Care (EPOC) criteria, non-controlled before-and-after studies and prospective cohort studies were considered eligible. Participants recruited from healthcare settings and studies measuring stewardship behaviours of healthcare professionals were excluded. Quality of studies was assessed using EPOC risk of bias criteria. Data were extracted and synthesized narratively. Registration: PROSPERO international prospective register of systematic reviews (PROSPERO 2016: CRD42016050343). Results: Twenty studies were included in the review with nine meeting the EPOC criteria. The overall risk of bias was high. Nineteen studies were conducted in high-income countries. Mass media interventions were most common ( n = 7), followed by school-based ( n = 6) and printed material interventions ( n = 6). Seventeen studies demonstrated a significant effect on changing knowledge, attitudes or the public's antimicrobial stewardship behaviours. Analysis showed that interventions targeting schoolchildren and parents have notable potential, but for the general public the picture is less clear. Conclusions: Our work provides an in-depth examination of the effectiveness of AMR interventions for the public. However, the studies were heterogeneous and the quality of evidence was poor. Well-designed, experimental studies on behavioural outcomes of such interventions are required.